Public’s preferences for health science popularization short videos in China: a discrete choice experiment - Xiao, Li; Min, Hewei; Wu, Yibo; Zhang, Jieyu; Ning, Yan; Long, Long; Jia, Kaixiang; Jing, Weilong; Sun, Xinying (Frontiers in Public Health, 2023)
Background: Health science popularization short video disseminates health information to the public in an understandable way about health information. Objective: To investigate the preferences of Chinese residents for health science popularization short videos and provide suggestions for optimizing the production of short videos. Methods: An online survey of Chinese people was conducted using a self-administered questionnaire, and a discrete choice experiment (DCE) was used to explore the public's preferences for health science popularization short videos. Results: A total of 618 respondents were included, of which 306 (45.51%) were male and 312 (50.49%) were female, 271 (43.85%) were aged 18-25, 239 (38.67%) were aged 26-60, and 108 (17.48%) were aged 60 and above. Whether the video is charged or not (46.891%) and the account subject (28.806%) were both considered important. The results of the DCE revealed that the participants considered video free of charge as the most significant attribute of health science popularization short videos (OR 3.433,. Overall, participants preferred and were more willing to pay for health science popularization short videos with a hospital account subject (OR 1.192,, with the form of graphic narration (OR 1.062, 95% CI 1.003-1.126), free of charge (OR 3.433,, with the content that satisfies their needs (very much needed: OR 1.253, 95% CI 95% CI 1.197-1.311; generally needed: OR 1.078, 95% CI 1.029-1.129), with platform certification (OR 1.041, 95% CI 1.011-1.073), without commercial advertisements (OR 1.048, 95% CI 1.018-1.080), with simple-to-understand content (OR 1.071, 95% CI 1.040-1.104), and with video content that evokes fear or dread of illness in the viewer (OR 1.046, 95% CI 1.015-1.078). Conclusions: Participants favor free health popularization short videos, which are hospital accounts, with content This is a provisional file, not the final typeset article that is illustrated, understandable, meets their needs, and can serve as a warning. In the future, the production of health popularization short videos should focus on improving the diversity and relevance of video content, making it as easy to understand to achieve good science popularization effects.